Aloperine suppresses the proliferation, migration and invasion of human liver cancer cells via induction of G2/M cell cycle arrest and inhibition of GROα expression. Issue 1 (1st January 2021) - Huang, Haijing; Cao, Yali; Huang, Lili; Lu, Renfei; Wang, Jian; Zhou, Yuan
Abstract : Aloperine has been shown to exhibit tremendous pharmacological potential. The present study was designed to investigate the effects of aloperine against human liver cancer cells and to explore the underlying mechanism. The results showed significant ( P  < .05) upregulation of GROα (GRO1 oncogene) in liver cancer tissues and cell lines. However, the expression of GROα significantly ( P  < .05) declined in liver cancer cells treated with aloperine (5 µM) which was concomitant with the inhibition of proliferation. Silencing of GROα significantly ( P  < .05) inhibited the proliferation of the liver cancer via G2 /M cycle arrest. Interestingly, aloperine also triggered G2 /M cell cycle arrest of the liver cancer cells. Nonetheless, the growth inhibitory effects of aloperine on liver cancer cells were attenuated by GROα overexpression and the cancer cells did not show the arrest of cell division. Additionally, aloperine also suppressed the migration, invasion and epithelial to mesenchymal transition of the human liver cancer cells via inhibition of GROα expression. Collectively, the findings revealed growth inhibitory effects of aloperine via suppression of GROα expression and point toward its therapeutic potential.